Diversity Initiatives in Higher Education: A Case Study from the University System of Georgia - Viverette, Maggie J. (Valdosta State University, 2011)
This study examined the responses of 1,546 senior survey participants on the National Survey of Student Engagement (NSSE) during the years 2005-2008 to analyze the influence of sex, race, and cohort as independent variables on student engagement in diversity activities at Valdosta State University. Using a Multivariate Analysis Of Variance (MANOVA) and a follow-up Analysis Of Variance (ANOVA), this study examined the NSSE responses of students enrolled as full-time seniors during the spring semester of each year for the years 2005-2008 on 11 diversity engagement variables selected as dependent variables. Results of the analyses revealed that there was no statistically significant influence by sex and by cohort, by sex and race, or by sex, race, and cohort. Of the three variables analyzed, only the variable of race was found to have an influence on 5 of the 11 dependent variables selected to represent diversity interactions. The analyses for the present research indicated that colleges should focus the largest number of activities for diversity interaction among its student population on the topic of race and incorporate activities to support discussion of other dimensions as secondary factors. Future researchers are encouraged to expand the study to include multiple institutions and to examine the influence of individual racial and ethnic categories on diversity interactions. Researchers are also encouraged to investigate the manner in which race influences the interaction and development of student participants.
Keywords: National Survey of Student Engagement; MANOVA; ANOVA; Gender; Cohort; Race; Diversity interactions; Minorities--Education (Higher)--United States